Desain Kurikulum SMK Negeri 8 Malang sebagai Lembaga Pembelajaran Karakter Disiplin Budaya Kerja (Studi Fenomenologi) - M. Odik Afifin (IPTPI Surakarta, 2022)
The increase in the unemployment rate by 9.27% was due to the workforce from vocational school graduates who had not been able to be absorbed optimally by the world of work. However, many graduates of SMK Negeri 8 Malang have the opportunity to immediately get a job after graduating in several leading DU/DI in Indonesia. The purpose of this study was to determine the curriculum design of SMK Negeri 8 Malang as a discipline character learning as a work culture institution with indicators of students' ability to be able to adapt and get used to completing work in the industrial world. This study was designed using a qualitative method and a phenomenological approach, namely research based on observations of subjective experience or phenomenological experience. The results showed that students were accustomed to completing assignments correctly and often some of them were able to complete theoretical and practical assignments before the deadline for submission. The integrated learning system of habituation of disciplined characters at SMK Negeri 8 Malang is very helpful for students in getting used to the world of work.